KONSEPTUALISASI DAN PILIHAN INSTRUMEN HUKUM POKOK-POKOK HALUAN NEGARA - Torik Abdul Aziz Wibowo (At-Tanwir Law Review, 2022)
The Main Principles of State Policy (PPHN) is an idea as an answer to the problems of Indonesia development wich caused by the ineffectiveness of the Development Planning System (SPPN) as a directive principles of state policy. This article attemps to answer two academic questions, first how the compatible concept of the Main Principle of the state policy with the Indonesia constitutional structure, and the second is wich approriate legal instrument for the Main Principle of the State Policy. The result of this research in this article describe that PPHN as the new directive principle of state policies must be able to answer the problem that contained by the Development Planning System; to ensure the implementation of sustainable development, PPHN must have juridical power by being regulated through statutory instrument; and PPHN must built within framework of presidential government system and regional autonomy. In addition constitution is the most suitable choice as an instrument for PPHN.